2023
DOI: 10.1111/1744-9987.14045
|View full text |Cite
|
Sign up to set email alerts
|

A nephrologist dream of peritoneal dialysis catheter with zero migration: A multicenter prospective study

Abdullah K. Al‐Hwiesh,
Ibrahiem Saeed Abdul‐Rahman,
Jose Carolino Divino‐Filho
et al.

Abstract: IntroductionPD catheter tip migration is a common complication and a significant cause of catheter malfunction. In this perspective, we present our experience with a new catheter and a new technique that involves the use of a new triple cuff PD catheter and a low entry site in an attempt to prevent PD catheter migration.MethodsA total of 503 incident PD patients have been studied in more than one PD center over a period of 5 years.ResultsDuring the 5‐year follow up we recorded zero percent catheter migration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, the three-cuff PDC is more complex to operate compared to conventional catheters, there is no routine clinical application currently. In addition, the three-cuff PDC and the right size dilator are difficult to obtain in many hospitals [ 26 ]. In our method, the use of a suture passer aimed to reduce additional trocar drilling, minimizing damage to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…However, the three-cuff PDC is more complex to operate compared to conventional catheters, there is no routine clinical application currently. In addition, the three-cuff PDC and the right size dilator are difficult to obtain in many hospitals [ 26 ]. In our method, the use of a suture passer aimed to reduce additional trocar drilling, minimizing damage to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…A logical concern is the compromise of lung capacities and volumes secondary to fluid infusion into the abdominal cavity; however, there is evidence showing that the effect on lung function is minimal [19]. Similarly, survival in critically ill patients is equivalent to other RRT techniques [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic procedures allow direct visualization of the peritoneal space and detection of adhesions. [5][6][7] Adhesiolysis is recommended if the surgeon determines that the adhesions are likely to impede catheter placement or hinder its proper function. 8,9 Previous research has shown that the risk of adhesions averaged 54% among individuals with prior abdominal surgery, but it varied considerably by the type of surgery.…”
Section: Introductionmentioning
confidence: 99%